A Bridge between Legacy Wireless Communication Systems and Internet of Things - Samer Jaloudi (IAES Indonesian Section, 2019)
The software-defined radio (SDR) is a flexible platform that can adapt to various wireless telecommunication frequencies. It is able to provide a reconfigurable communication infrastructure for wireless systems. Hence, SDR is proposed here as a bridge between legacy wireless communication systems and the Internet of Things (IoT) via standard telecommunication protocols. The standard protocols are hypertext transfer protocol (HTTP), simple mail transfer protocol (SMTP), and message queuing telemetry transport (MQTT). Data collected from legacy wireless systems have been formatted via JavaScript object notation (JSON) for interoperability and categorized according to the application and the communication pattern. The extracted data are then transferred over MQTT for machine-to-machine (M2M) communication, over SMTP for machine-to-human (M2H) notification, and over HTTP for human-to-machine (H2M) communication. However, received audio signals from FM-based broadcasting stations have been transferred to the Internet servers over extensible messaging and presence protocol (XMPP), in live audio streaming. The objective is to introduce an SDR-IoT bridge that is inexpensive, scalable, and interoperable. The analyses show that the environment has good-performance, and can be used for many applications of smart city sectors, for Internet Radio, and for Internet-based monitoring of airplanes and vessel navigation.